O livro-objeto Pau Brasil - Judar, Tânia Veiga (2016)
This dissertation discusses the Pau Brasil work, written by Oswald de Andrade, and published in 1925, from the perspective of its configuration as an object book, that is, one that is part of visual arts and literature. Therefore, the research highlights the connection between the poetry of Oswald de Andrade and the artistic work of Tarsila do Amaral, as well as the graphic and conceptual design of such work. In the face of the innovative trends of the late nineteenth century and of the early twentieth century vanguards, and the cultural context lived by the author, the Pau Brasil work and the artistic and literary procedures that form it were analyzed, in order to establish a significant interarts dialogue. In order to contextualize and to support the study, aspects of the creation of the object book were addressed, assessing the difficulties of its conceptualization, as well as the connections established with the artistic vanguards - Futurism, Cubism, and particularly, Dadaism - and with works that, in a certain way, anticipated some of the characteristics of the Pau Brasil object book. The analysis of poems "enlightened" by Tarsila drawings unfolded the object book nature of Pau Brasil to the extent that the book is configured as a hybrid body, prepared with mixed and unusual materials when compared with the concept of poetry books – daily speeches fragments, advertisements, colonial history books excerpts, illustrations - in which the printing graphic materiality, the poems, the cover and the drawings are "aesthetic facts" not only to be read and seen, but to be touched and handled in a critical-parodic set